2002
DOI: 10.1161/01.cir.0000031525.61826.a8
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Progenitor Cells in Human Blood

Abstract: Background-Recent animal data suggest that vascular smooth muscle cells within the neointima of the vessel wall may originate from bone marrow, providing indirect evidence for circulating smooth muscle progenitor cells (SPCs). Evidence for circulating SPCs in human subjects does not exist, and the mechanism whereby such putative SPCs may home to sites of plaque formation is presently not understood but is likely to involve expression of specific surface adhesion molecules, such as integrins. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
338
5
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 459 publications
(369 citation statements)
references
References 30 publications
19
338
5
4
Order By: Relevance
“…During development, most smooth muscle progenitors arise mainly from the splanchnic mesoderm and from the neural crest (15). At postnatal life, progenitors for SMC have been found in circulating blood (16) and bone marrow (17). Bone marrow has been the hallmark site in postnatal life known to harbor at least two populations of stem cells: the hematopoietic and the nonhematopoietic mesenchymal stem cell (MSC).…”
Section: Discussionmentioning
confidence: 99%
“…During development, most smooth muscle progenitors arise mainly from the splanchnic mesoderm and from the neural crest (15). At postnatal life, progenitors for SMC have been found in circulating blood (16) and bone marrow (17). Bone marrow has been the hallmark site in postnatal life known to harbor at least two populations of stem cells: the hematopoietic and the nonhematopoietic mesenchymal stem cell (MSC).…”
Section: Discussionmentioning
confidence: 99%
“…55) Since the existence of smooth muscle progenitor cells (SMPCs) was described by Simper et al, attention has focused on the finding that SMPCs have opposite role to EPCs in the development of several vascular diseases. 59) Recently, our laboratory found that the CD34 + VEGFR2 + cells were closely involved in the intimal thickening of the supraclinoid internal carotid artery collected from adult patients with moyamoya disease. 61) This study was interesting in that certain progenitor cells also participated in the progressive occlusive lesion in moyamoya disease.…”
Section: Epcmentioning
confidence: 99%
“…MNCs were then resuspended in endothelial cell growth medium-2, placed on a 6-well plate coated with collagen type I (Becton Dickinson), and grown in culture as previously described. 8 …”
Section: Buffy Coat Preparation and Endothelial Cell Culturementioning
confidence: 99%
“…7 These latter cells have many of the characteristics of progenitors undergoing multiple population doublings and exhibit an angioblastic phenotype. 8 In a series of elegant experiments, Lin and colleagues 7 have also shown that CECs originate from the adult vessel wall, whereas EPCs most likely derive from circulating angioblasts.…”
mentioning
confidence: 99%